2015
DOI: 10.1073/pnas.1501835112
|View full text |Cite
|
Sign up to set email alerts
|

Cells transplanted onto the surface of the glial scar reveal hidden potential for functional neural regeneration

Abstract: Cell transplantation therapy has long been investigated as a therapeutic intervention for neurodegenerative disorders, including spinal cord injury, Parkinson’s disease, and amyotrophic lateral sclerosis. Indeed, patients have high hopes for a cell-based therapy. However, there are numerous practical challenges for clinical translation. One major problem is that only very low numbers of donor cells survive and achieve functional integration into the host. Glial scar tissue in chronic neurodegenerative disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 59 publications
2
53
0
2
Order By: Relevance
“…A number of reports supporting the role of scar tissue as a barrier have shown that its removal facilitates neural restoration [1618]. However, recent studies have also suggested that scar tissue is not necessarily an obstacle for regeneration and may even be necessary for neural restoration [19]. In the present work, we demonstrated that INDP alone promotes motor recovery, although this effect is augmented with glial scar removal.…”
Section: Discussionsupporting
confidence: 57%
“…A number of reports supporting the role of scar tissue as a barrier have shown that its removal facilitates neural restoration [1618]. However, recent studies have also suggested that scar tissue is not necessarily an obstacle for regeneration and may even be necessary for neural restoration [19]. In the present work, we demonstrated that INDP alone promotes motor recovery, although this effect is augmented with glial scar removal.…”
Section: Discussionsupporting
confidence: 57%
“…Whereas glial scars are neuroprotective (against severe inflammation) they also inhibit axon regrowth (Frisén et al, ; Liu et al, ; Rowland, Hawryluk, Kwon, & Fehlings, ). Despite numerous efforts to reduce the negative impact of the glial scar, improvements to functional recovery remain limited (Sekiya et al, ; Shen, Wang, & Gu, ; Zhao & Fawcett, ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the abundance of data showing that reactive astrocytes can, indeed, form a barrier to highly invasive glioblastoma as well as oligodendrocyte progenitor cells (Lau et al, 2012;Keough et al, 2016), macrophages (Wanner et al, 2013), neural precursor cells (Karimi-Abdolrezaee et al, 2010), auditory neuroblasts (Sekiya et al, 2015), fibroblasts (Wanner et al, 2008), Schwann cells (Fouad et al, 2005;Kanno et al, 2014) and regenerating olfactory sensory and other axons (Anders and Hurlock, 1996;Silver and Miller, 2004;Zhang et al, 2006;Schachtrup et al, 2010;Cregg et al, 2014), it seems likely that they could at least participate in the formation of an additional constraint to severed axons after spinal cord injury as they encircle the lesion core.…”
mentioning
confidence: 99%
“…In the special case of a very narrow lesion when core cells are lacking and there is less need to "corral" them (Wanner et al, 2013), scar forming astrocytes may be made permissive in response to the presence of an abundance of robustly growing axons . It was also made clear beginning long ago that reactive astrocytes can be a substrate for axonal outgrowth under the right circumstances (Reier, 1979;Silver and Ogawa, 1983;Smith et al, 1986;Hoke et al, 1994;McKeon et al, 1995;East et al, 2010;Sekiya et al, 2015) and, therefore, it should have been no surprise that they could serve as a permissive substrate into the lesion (which is clinically irrelevant) when axons were highly stimulated and especially before the glia became hyper dense. Thus, in the fashion of a drawbridge, reactive scar astrocytes can be either a barrier or, on occasion, a roadway depending on the conditions present normally or created experimentally inside or outside of the lesion penumbra.…”
mentioning
confidence: 99%